تعلیم المعلومات والمکتبات فى المملکة العربیة السعودیة وتوجهاته المستقبلیة :دراسة وصفیة تحلیلیة - د. سعد بن سعید الزهیرى (المجلة الدولية لعلوم المكتبات والمعلومات)
This paper aims at presenting an overview of I&LS education in theSaudi Arabia. It should also provide a description of its current situation as wellas exploring its future, especially while many of LIS Academic departments havechanged their names from LIBRARY AND INFORMATION to informationscience, information studies or Information Management. In fact, manyothers are in the same process. This paper will also explore opinions of leadersof those Depts., regarding where they are heading when changing theiraffiliations. Some have moved from colleges of Arts or Social Sciences toComputer & Information colleges, while some think to move to AdministrationColleges. Third dimension is going to check up on the subjects that thoseDepartments will concentrate on. Some of them have chosen to concentrate onKnowledge management, or information management. Some think that digitalarchiving is needed highly in work market. Coordination between Departments ishighly needed so that they don't end up as a copy of each other. Paper at handshall study situation using descriptive method with many tools in order to answerresearch queries. Study concludes with exploring opinions of faculty members ofthose I&LS Depts. On the degree that those Departments are accomplishing tohelp Saudi Arabia 2030 Vision.Study found that Information & Library Sciences Academic Departmentsin Saudi Arabia support Country’s 2030 Vision by providing country with bachelor,master and Ph.D. graduates in a very important specialty. Study also found thattraditional stereotypes of “library” field is considered one of the most challengesthat face these Depts., which require them to change their names, develop theirplans and enhance their image within academic arena and in country as a whole.Students joining departments lack English and in IT skills which make tasks moredifficult to enhance quality of products. University respect to these Depts. isconsidered another challenge that these Depts. have to face, as well as scarcityof jobs for graduates. In regards to coordination responsibility between  departments, participants in study think that Association for Library & Informationas well as Under Secretary of Education Ministry are proposed. Study found thatchanges of names are encouraged by respondents.Study recommends that a national strategy for these Depts. is needed sothat overlapping get minimized when reshaping of these Depts. is undertaken.Coordination between these Depts. is recommended also to cover all neededareas for the Nation, and to avoid being a copy of each other. A study of jobsmarket is remmended so that education plans take this into consideration. LISDepts. are encouraged to join IFLA, AFLI, SLA/AGC and iSchools.